UPAYA PEMERINTAH KOTA DENPASAR DALAM MENGATASI LINGKUNGAN PERUMAHAN DAN PERMUKIMAN KUMUH DI KOTA DENPASAR - Putra Prabawa, A. A. Ngurah; -, Marwanto (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013)
Residential neighborhoods and slums in the city of Denpasar arise as a result ofpoverty and urbanization. Denpasar city Government seeks to address the housing andslum neighborhood whose location does not meet the occupancy requirements of bothtechnical and non-technical. The problem that arises is what is the basis forconsideration of Denpasar Government against the stipulation of a residentialneighborhood and the location of slums and what efforts were made by the Governmentin addressing Denpasar residential neighborhoods and slums in the city of Denpasar.The conclusion in the discussion of this issue is the Denpasar Government establishedthe location of residential neighborhoods and slums under Law No. 1 of 2011 onHousing and Settlement Zone, Act No. 4 of 1992 on Housing and Slum Areas, LocalRegulation of Denpasar No. 27 Year 2011 on Spatial Planning of Denpasar and basedon the level squalor and slums count levels. In addressing slum housing environment bycreating as control program Detail Spatial Plan, Zoning Regulations and Incentivesand Disincentives mechanism. Discussing this the issue of empirical legal researchmethods used to study the nature of descriptive.
Keywords: Governance, Spatial, Environmental, Slum